Evaluation of Existing Materials Used in Wind Turbine Blade Construction: Assessing their Structural Characteristics, Sustainability and Performance (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2024)
The study investigatedthe existing materials used in wind turbine blade construction: assessing their structural characteristics, sustainability and performance.The study employed Finite Element Analysis (FEA) to assess various materials' performance, considering factors such as deformation, stress, and safety. Materials examined include Aluminum 2024-T4, Carbon Fiber-Reinforced Polymer (CRFP), Glass Fiber-Reinforced Polymer (GRFP), Bamboo, Aramid Fiber, Pine, and Glulam. The analysis covered a range of angular velocities to simulate real-world conditions. Results indicated that material choice significantly impacts blade performance. The study acknowledges limitations such as simplified environmental conditions, limited consideration of moisture effects, and the absence of fatigue and thermal studies. Recommendations include future research in Computational Fluid Dynamics (CFD) analysis, geographical-specific designs, and advanced materials research. Finally, this work underscores the importance of sustainable material choices in wind turbine blade design. The findings offer valuable insights for engineers, researchers, and policymakers seeking to advance wind energy technology with environmental responsibility at its core. In conclusion Wind energy is a pivotal player in the global transition towards sustainable power generation. Wind turbines, specifically their blades, constitute the driving force behind this transformation. The selection of materials for these blades is a crucial endeavor, entailing a delicate balance between sustainability, performance, and cost-effectiveness. In this pursuit, sustainability is a lodestar guiding the way.One of the recommendations made was that tailoring material choices to specific wind energy projects is essential.